IMPLEMENTASI PERATURAN DIREKSI PT PLN (PERSERO) NOMOR 088-Z.P/DIR/2016 TENTANG PENERTIBAN PEMAKAIAN TENAGA LISTRIK (P2TL) WILAYAH RIAU (STUDI KASUS RAYON BARAT KOTA PEKANBARU) - Nanang Kurniadi; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
A large company as an electricity provider for the community is PT. The State Electricity Company (PT. PLN), where the state-owned electricity company has contributed greatly in distributing electricity needs to the community. As a state-owned company that deals with the issue of electricity interests and provides a large amount of electricity supply to the public in Indonesia, of course PT. PLN provides maximum service for the benefit and progress of the nation. P2TL is carried out based on the Decree of the Board of Directors of PT PLN (Persero) Number 088-Z.P / DIR / 2016 concerning Controlling the Use of Electric Power, Subsequent Billing and Termination of Electric Power Connection. P2TL is a decision that generally regulates technical matters in the implementation of regulating electricity usage routinely by each PLN Rating / Rayon, PLN Branch, Regional PLN / Distribution structurally in accordance with the description of the main tasks and their respective organizationsThe research was conducted using qualitative descriptive research methods. This study uses the concept of the Grindle Theory in Subarsono (2012: 92), namely the implementation of policies consisting of the contents of the policy: the interests of the target group, the type of benefits, the degree of desired change, the location of decisions, the implementation of decisions, the resources involved. Environment Implementation: Power, interests and strategies of the actors involved, Characteristics of institutions and regimes in power, Level of Compliance and responsiveness. In this research, the techniques used were Observation, Interview, and Literature Study using descriptive analysis.The results of this study indicate that the implementation of P2TL at PT. PLN West Rayon of Pekanbaru City cannot be said to be optimal seen from the discussion of the Grindle Theory in Subarsono. The existence of several indicators that are very influential in the implementation in the field from HR to Resources supporting technology in P2TL Implementation.Keywords: Implementation, Regulation, Control